2017
DOI: 10.1002/term.2397
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive injectable aggregates with nanofibrous microspheres and human dental pulp stem cells: A translational strategy in dental endodontics

Abstract: Regeneration of the pulp-dentin complex with stem cells is a potential alternative to conventional root canal treatments. Human dental pulp stem cells (hDPSCs) have been extensively studied because of their ability to proliferate and differentiate into mineralized dental and non-dental tissues. Here we combined hDPSCs with two types of injectable poly-L-lactic acid (PLLA) microsphere with a nanofibrous or smooth surface to form bioactive injectable aggregates, and examined their ability to promote pulp regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
4
12
0
Order By: Relevance
“…In the present work, novel models of bioengineered skin generated by using four MSC types were described. In agreement with previous reports, suggesting that heterotypical bioengineered tissues have low levels of differentiation while kept in vitro (Garzon et al, 2013;Garzon et al, 2009a), in vitro tissues had very few cell layers on top of the dermis substitute -although the number of cell layers tended to increase with time -and a complete absence of differentiation markers, such as rete ridges and chorial papillae or keratinisation.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present work, novel models of bioengineered skin generated by using four MSC types were described. In agreement with previous reports, suggesting that heterotypical bioengineered tissues have low levels of differentiation while kept in vitro (Garzon et al, 2013;Garzon et al, 2009a), in vitro tissues had very few cell layers on top of the dermis substitute -although the number of cell layers tended to increase with time -and a complete absence of differentiation markers, such as rete ridges and chorial papillae or keratinisation.…”
Section: Discussionsupporting
confidence: 92%
“…An interesting phenomenon was that BMSCs showed slight CK10 expression in vitro, but this expression was initially negative in vivo and became positive at 30 d. This finding may be explained as an adaptive process of the cells, which could partially lose their original orientation in vivo and, thus, minimise their expression profile until the epithelium became fully differentiated. These results, related to the in vitro differentiation potential of WJSCs and BMSCs, were in agreement with previous work demonstrating their keratinocytic differentiation capability (Garzon et al, 2013) and with the fact that ADSCs and DPSCs have not yet been differentiated into skin keratinocytes -although reports have suggested that these cell types may have epithelial differentiation capability in the presence of inductive medium (Baer et al, 2013;Dogan et al, 2015). In the present study, both WJSCs and BMSCs were able to develop a larger number of cell layers at the in vitro stage, which coincided with the early cytokeratin expression.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations